Distribusi Kerentanan Seismik di Wilayah Pusat Kota Surabaya - Dzikrullah Akbar; Mohammad Syamsu Rosid; Aina Najwa Darmanto (Jurnal Penelitian Pendidikan IPA, 2024)
Surabaya is the second major city of Indonesia and the economic capital of eastern Indonesia. The city’s central area is the governmental center of East Java Province. This area is traversed by the Surabaya section of the Kendeng Fault which could potentially generate a maximum M6.5 earthquake. The East Java megathrust zone also threatens this area with a potential maximum magnitude of M8.9 earthquake. The rock geology of this region is dominated by soft alluvial soil which could amplify earthquake shaking. This study aims to identify the distribution of seismic vulnerability index in Surabaya’s central area. Therefore, microtremor measurements were carried out at 61 points in this area. The results were then analyzed using the Horizontal to Vertical Spectral Ratio (HVSR) method to determine the amplification factor values and seismic vulnerability index. The results of the HVSR analysis show that the amplification factor value and seismic vulnerability index are in the low to medium category ranging from 0.8370 - 3.8298 and 0.6041 - 14.6268, respectively. The distribution of the results shows that the northern area is more vulnerable than the southern part. This is verified by the geological conditions of the northern part which is dominated by alluvial soil.